Fast Measurements of Adsorption on Porous Materials Using Jäntti's Method - Erich Robens; Carel H. Massen; Johannes A. Poulis; Piotr Staszczuk (Adsorption Science & Technology)
In 1972, Jäntti et al. formulated a method to shorten the time taken for adsorption measurements. We suggested at the Kiev International Conference on Vacuum Microbalance Techniques (1999) that the applicability of this method could be widened by considering a number of parallel adsorptions. There is, however, a more complicated but perhaps more interesting variant possible when extra mass transport is considered to occur in series. Such an application could involve adsorption within a porous structure where diffusion must be considered as a process occurring in series with adsorption on the surface.